A simplified non-linear modelling strategy to generate fragility curves for old masonry buildings - Stocchi, Alessandro; Giry, Cédric; Capdevielle, Sophie; Zentner, Irmela; Nayman, Emmanuelle; Ragueneau, Frédéric (Computers & structures, 2021)
•Modelling the global nonlinear response of masonry structures.•An efficient numerical method to compute fragility curves.•Fragility curves derived for a large dataset of structures in a typology.•A global structural damage indicator based on the eigenfrequency drop off. In the context of historical seismology, studying the behaviour of historic masonry buildings is of great importance, as they are witnesses of past events. While interesting methods can be found in the literature to assess the seismic vulnerability of masonry structures subject to strong earthquakes, the topic of moderate seismicity, as encountered in many European countries, is still to be investigated. The present work proposes a global methodology to build fragility curves for existing masonry buildings. An efficient computational method to address the non-linear response of masonry structures is presented. The method is based on the modal decomposition of the structural response. An equivalent non-linear single degree of freedom oscillator is identified for the main modes. The modelling strategy enables to carry out numerous computations with a low computational effort, allowing for a probabilistic approach. To build fragility curves, a damage indicator based on the frequency shift is chosen. To validate the proposed approach, the simplified model of a real masonry building is compared to a full non-linear time history analysis. The method is eventually illustrated by the derivation of fragility curves for industrial masonry buildings.